Cryoablation of small kidney tumors. (December 2016) - Zondervan, P.J.; Buijs, M.; de la Rosette, J.J.; van Delden, O.; van Lienden, K.; Laguna, M.P.
Abstract: Introduction: Cryoablation (CA) has been broadly used mostly in the treatment of small renal masses (SRMs). The present review aims to define the current role of CA in the treatment of SRMs by assessing clinical indications and outcomes. Method: A comprehensive review on patient selection, procedural details, perioperative complications, and short/long-term oncological and functional outcomes was conducted. For each section, a take-home message was formulated with level of evidence (LoE) according to Cochrane collaboration. Results: Age and comorbidity drive the choice of ablation in SRMs, although hospital setting also influences the decision. Technically in adequate CA or first post-CA control occurs in 3–5% of laparoscopic cryoablation (LCA) or percutaneous cryoablation (PCA) series. Meta-analysis does not evidence differences in the rate of residual tumor per person-year between the approaches (0.033 LCA vs. 0.046 PCA, p  = 0.25). Perioperative complications (8–25%) are erratically reported. LCA has significantly lower likelihood of complications than minimally invasive partial nephrectomy (MIPN). Systematic reviews indicate 30-month local tumor progression rate of 8.5% for LCA in renal cell carcinoma but low metastatic progression (1–4.4%). Few LCA long-term follow-up series (mean/media 48–98 months) report recurrence-free survival (RFS) and cancer-specific survival (CSS) ranges of 80–100%. For PCA, Kaplan–Meier local disease-free survival (DFS) of 95.6% at 3–5 years [32] and 5-year overall survival and local RFS of 86.3% were reported. The decrease in renal function after CA is minimal, and the only risk factor associated is the basal estimated glomerular filtration rate (eGFR). Conclusion: LoE 3a/b confirms lower CA perioperative complication rate and higher local progression rate than those for MIPN. CA preserves postoperative renal functional, without any evidence of differences in mid-/long-term follow-up compared to nephron sparing surgery. Highlights: CA is an efficient treatment for SRMs in selected cases. No differences in outcomes exist between laparoscopy or percutaneous approach. CA entails lower complication rate than partial nephrectomy but higher risk of local recurrence. In primary small RCCs, the rate of metastatic disease is ≤ 2% and CSS close to 100%. CA preserves renal function; decrease in eGFR is determined by basal renal function.